Ethnobotanical study on plant leaves for food wrapping in traditional markets of Wonosobo District, Central Java, Indonesia - ARYA ARISMAYA METANANDA; WHISNU FEBRY AFRIANTO; LAELI NUR HASANAH; YASRI SYARIFATUL AINI; AFNIDA SHOFFATI NOORFAJRIA (Society for Indonesian Biodiversity, 2023)
Abstract. Metananda AA, Afrianto WF, Hasanah LN, Aini YS, Noorfajria AS. 2023. Ethnobotanical study on plant leaves for food wrapping in traditional markets of Wonosobo District, Central Java, Indonesia. Biodiversitas 24: 3803-3813. Currently, almost all items in our daily life are made from plastic, such as food packaging, household appliances, drink bottles, and plastic bags. The use of plastic packaging can harm the environment and human health. Plant leaves for food wrapping can be an alternative to reduce these impacts. Indonesia has many cultures, philosophies, and social activities related to using plant leaves for food wrapping. This study aimed to document public knowledge about plant leaves for food wrapping in the traditional markets of Wonosobo District, Central Java Province, Indonesia. This study used the purposive sampling technique to select 41 informants for the interviews. A total of 10 plant leaves species belonging to 7 families were used for food wrapping by traders in the traditional markets of Wonosobo District. The ten species were Musa spp., Tectona grandis, Cocos nucifera, Artocarpus heterophyllus, Artocarpus camansi, Ficus septica, Hibiscus tiliaceus, Pandanus amaryllifolius, Cordyline fruticosa, and Alocasia macrorrhizos. These trees dominate plant growth forms in this study. The leaves of these different plants were used as food plates and wraps for multiple dishes. Efforts are needed to reduce plastic use in the traditional markets by making regulations to minimize or substitute with plant leaves.